Police Officer Perceptions of Non-consensual Dissemination of Intimate Images - Zvi, Liza; Shechory-Bitton, Mally (Frontiers in Psychology, 2020)
Non-consensual dissemination of intimate images (NCII) is a major concern in many countries. The increase in the number of NCII cases and awareness of its adverse effects on victims has raised public awareness, with many states enacting legal and non-legal measures to combat this new type of violence. Yet despite recent legislation there is reason to suspect that the majority of NCII cases remain unreported. Thus research is needed on law enforcement perceptions of victims and identification of victim-blaming attitudes and factors that might affect legal decision-making. The present study addressed this issue by focusing on Israeli police officer perceptions of NCII victims and offenders: 145 police officers and 160 students, who served as a control group, were presented with a scenario depicting an NCII offence in which the stolen intimate material was either self-generated by the victim (selfies) or stealth-taken by the victim's ex-boyfriend. In both cases, the stolen images were disseminated by the ex-boyfriend without the victim's permission. The findings indicated victim-blaming attitudes toward NCII victims within law enforcement as well as an effect of the source of stolen images. Although officers perceived NCII as criminal and the offender as highly culpable and punishable, they engaged in victim-blaming. This was especially the case for the self-taken scenario, which elicited negative feelings and less empathy toward the victim. The relevance of emotions in legal contexts is emphasized in light of their contribution to the participants' punitive judgments. Victim-blaming in NCII offences and its implications are discussed and suggestions are made for how to reduce negative and victim-blaming attitudes among law enforcement.